Relationships Between Indoor Air Pollution and Psychrometric and Effective Factors in the Polyurethane Factories with Emphasis on Methylene Diphenyl Diisocyanate - S. Etemadi Nejad; M. Rokni; S.M. Asadi; Seyedtaghi Mirmohammadi (Iranica Journal of Energy and Environment, 2011)
The object of this study is determination of the relationship between airborne methylene diphenyl diisocyanate (MDI) and selective psychrometric variables. The production of MDI factories were polyurethane adhesives, paints and varnishes and the workers were exposed to MDI in the indoor air. The air samples were collected by midget impinger and multiple regressions model was used to determine the relationship between variables. All of the samplers (midget impinger) were connected to mini personal sampler pump fixed toworkstations near the source of pollution based on NIOSH method 5522. The first step in the analysis of a solution is derivatization of isocyanates for the separation through HPLC, for their qualitative as well as quantitative analysis. Air sampling and analysis was performed according to (NIOSH) method 5522 for diisocyanate in air. The results revealed that a correlation between MDI concentration and relative humidity, dry bulb temperature, altitude and dimension of polyurethane factories. Dimension of factories yields reasonable negative relationship, the MDI concentration was ranged from 93.8 to 99(μg/m3) and statistically significant at 0.0001 level and the relative humidity was ranged from 42.6 to 45% and dry bulb temperatureranged from 28 to 29°C were statistically significant at 0.035 and 0.0001 level, respectively. A statistical predictive model was obtained from multiple regression modeling for MDI and psychrometric parameters. The result of the current study may be useful for the prediction of diisocyanate pollution for polyurethane factoriesin the same psychrometric condition. This indicates that the MDI concentration is attributed to psychrometric parameters.